2002
DOI: 10.1046/j.1439-0442.2002.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Testing of Immunological Effects of a Phytomedicinal Combination (EquiMun) and its Compounds on Bovine Leucocytes

Abstract: One of the major goals of this study was to establish fast, reliable and sensitive assays for the quality control of immunomodulating phytopreparations and to determine whether pharmacological compounds or phytopreparations have effects on bovine immune cells. Flow cytometric methods were chosen because they are very sensitive in the detection of even subtle effects on cells. In this study, we addressed the question of whether these methods are useful in monitoring the effects of EquiMun and its compounds on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…There are numerous recent reports indicating the immunostimulating or modulating effects of various preparations and extracts (Stimple et al 1984;Burger et al 1997;See et al 1997;Sun et al 1999;Currier and Miller 2001;Goel et al 2002). There are a few reports of the veterinary application of Echinacea therapy, for example, in horses (O'Neill et al 2002 ), swine (Stahl et al 1990) and cattle (Schuberth et al 2002) . Nothing has been reported on its use in poultry.…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous recent reports indicating the immunostimulating or modulating effects of various preparations and extracts (Stimple et al 1984;Burger et al 1997;See et al 1997;Sun et al 1999;Currier and Miller 2001;Goel et al 2002). There are a few reports of the veterinary application of Echinacea therapy, for example, in horses (O'Neill et al 2002 ), swine (Stahl et al 1990) and cattle (Schuberth et al 2002) . Nothing has been reported on its use in poultry.…”
Section: Resultsmentioning
confidence: 99%
“…In some studies carried out in animal fields, the influence of medical plants on improvement of immune system had been reported (Rivera et al, 2003;Schuberth et al, 2002). Furthermore, Rahimi et al (2011) reported that dietary thyme extract (0.1%) soluble in water did not affect immune system, but relative weight of bursa fabricius was significantly affected by garlic group and antibody response to SRBC was higher in coneflower group when compared with control group (P<0.05).…”
Section: The Effect Of Different Treatments On Relative Weight Of Immmentioning
confidence: 99%
“…Mohammad et al (2013) reported that, inclusion of savory essential oil for 21 days (21-42 days) in diet of heat stressed broilers had no significant effect on lymphoid organs (spleen, thymus, bursa of Fabricius) weight and our findings confirm it. Besides, in some studies performed in animal fields, the influence of medical plants on improvement of relative weights of different organs had been reported (Rivera et al, 2003;Schuberth et al, 2002). Additionally (Rahimi et al, 2011) reported that the dietary thyme extract (0.1%) soluble in water affected relative weight of bursa of fabricius of broilers significantly.…”
Section: Discussionmentioning
confidence: 99%